Correction to: Regional disparities in the flow of access to breast cancer hospitalizations in Brazil in 2004 and 2014 - Beatriz Castro de Souza; Francisco Winter dos Santos Figueiredo; Luiz Vinicius de Alcantara Sousa; Erika da Silva Maciel; Fernando Adami (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.